Determining Ways of Thinking and Understanding Related to Generalization of Eighth Graders - Gülçin Oflaz; Handan Demircioğlu (International Electronic Journal of Elementary Education, 2018)
The main purpose of this study is to determine ways of thinking and understanding of eight graders related to generalizing act. To carry out this aim, a DNR based teaching experiment was developed and applied to 9 eight graders. The design of the study consists of three stages; preparation process in which teaching experiment is prepared, teaching process in which teaching experiment is applied, and analysis pro-cess in which continuous and retrospective analyses are carried out. Analysing the data, it was found that students’ ways of thinking could be determined as relating, searching, and extending. Ways of understanding belonging to generalizing act could be determined as identification, definition, and influence. It was recommended to add two new categories “relating with an authority” and “searching the same piece” to the generalization taxonomy.